Severe hair loss associated with psychotropic drugs in psychiatric inpatients-Data from an observational pharmacovigilance program in German-speaking countries - Druschky, Katrin; Bleich, Stefan; Grohmann, Renate; Burda, Katharina; Frieling, Helge; Hillemacher, Thomas; Neyazi, Alexandra; Stuebner, Susanne; Toto, Sermin (European Psychiatry, 2018)
BACKGROUND: The study aimed to investigate severe hair loss related to psychotropic drugs (PDs) by using data from the drug safety programme Arzneimittelsicherheit in der Psychiatrie (AMSP). METHODS: Data on PD utilization and reports of severe PD-related hair loss were collected in 83 psychiatric hospitals in Austria, Germany and Switzerland during the period 1993-2013. RESULTS: Out of 432,215 patients under surveillance, 404,009 patients were treated with PDs for the main indications of depression, schizophrenic disorder, neurosis, mania, and organic psychosis. Severe hair loss related to PD treatment was reported in 43 cases (0.01%). The rates of hair loss under antipsychotic drugs were slightly lower than the mean rates of all PDs and antidepressant drugs. Valproic acid was related to the highest risk. In 6 of the 43 cases, hair loss was imputed to multiple drugs, with 4 cases imputed to double drug combinations and 2 cases to triple combinations. Rates of severe hair loss under valproic acid (VPA) and lithium salts were distinctly lower as compared with the overall rates reported in literature. Severe hair loss under PD treatment was reported significantly more often in female patients than in male patients (p < 0.01). CONCLUSION: The rate of severe PD-related hair loss was very low in the present survey. The large number of patients included in this multicentre study allows for assessment and comparison of hair loss rates related to different PDs and groups of PDs and provides new and supplementary information on PD-related hair loss.
EVALuna2:36385